Kandungan Mineral dan Struktur Kristal Batu Sekis - Muhamad Ragil Setiawan; Rahmat Nawi Siregar (SPEJ (Science and Physic Education Journal), 2020)
This study aims to determine the mineral content and crystal structure of schist rocks in South Lampung. The method used in this research is the X-ray diffraction method to see the lattice parameters and the crystal structure of the schist rocks. Based on data processing, information was obtained that two main minerals were found, namely quartz and albite minerals. In conclusion, the Albit minerals found in the two samples of rock crystal schists in South Lampung have the same crystal structure and lattice parameters, while the quartz minerals from the two samples have different crystal structures and lattice parameters. Keywords: Lampung, Schis, XRD, Crystal Structure